2022
DOI: 10.1002/path.5880
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin 1 is a serum biomarker and potential therapeutic target for HBV‐associated liver fibrosis

Abstract: Stanniocalcin 1 (STC1), a secreted protein, is upregulated in human cancers including hepatocellular carcinoma (HCC). While most HCCs develop from chronic liver disease, which involves progressive parenchymal injury and fibrosis, the role of STC1 in this preneoplastic stage remains poorly understood. In this study we investigated the clinical relevance and functional significance of secreted STC1 in liver fibrosis. To this end, the STC1 level was determined in the serum samples of chronic hepatitis B patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Genes represented in our TRS include five members predicted to be secreted proteins according to The Human Protein Atlas (https://www.proteinatlas.org), which could be explored further in suitably well-annotated clinical samples. Although not previously reported in NAFLD, CHRDL2 is upregulated in a range of tumour tissues including HCC 43 , while STC1, CTGF 44 , GDNF and FGF7 are all linked to hepatic fibrogenesis 45,46 . Additionally, STC1 is a potential serum biomarker for hepatitis B virus-associated liver fibrosis 45 and secreted FGF7 47 may be a prognostic marker in cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Genes represented in our TRS include five members predicted to be secreted proteins according to The Human Protein Atlas (https://www.proteinatlas.org), which could be explored further in suitably well-annotated clinical samples. Although not previously reported in NAFLD, CHRDL2 is upregulated in a range of tumour tissues including HCC 43 , while STC1, CTGF 44 , GDNF and FGF7 are all linked to hepatic fibrogenesis 45,46 . Additionally, STC1 is a potential serum biomarker for hepatitis B virus-associated liver fibrosis 45 and secreted FGF7 47 may be a prognostic marker in cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 69%
“…Although not previously reported in NAFLD, CHRDL2 is upregulated in a range of tumour tissues including HCC 43 , while STC1, CTGF 44 , GDNF and FGF7 are all linked to hepatic fibrogenesis 45,46 . Additionally, STC1 is a potential serum biomarker for hepatitis B virus-associated liver fibrosis 45 and secreted FGF7 47 may be a prognostic marker in cholangiocarcinoma. The predictive model requires external validation, ideally in prospective longitudinal studies.…”
Section: Discussionmentioning
confidence: 69%
“…Genes preferentially or specifically dysregulated by CCl 4 in the fibroblast subpopulation include a 174-fold induction of Sectm1a, which stabilizes tissue resident macrophages in response to acute inflammation 103 , and a 160-fold suppression of Nkx6-1, an unfavorable prognostic marker for human hepatocellular carcinoma 104 . Genes specifically dysregulated in VSMCs include Stc1, a classic inflammation marker in fibrotic disease 105 , as well as lnc24481*, which was up regulated 16-fold, and lnc43318, which was 5- fold down regulated by CCl 4 exposure. HSCs showed the most extensive dysregulation, impacting 1,296 genes (743 PCGs, 553 lncRNAs lncRNAs), >90% of which were specifically dysregulated in HSCs (Table S6A).…”
Section: Resultsmentioning
confidence: 99%
“… 27 Previous reports revealed roles of STC1 in fibrosis of the kidney, 28 lung 29 and liver. 30 Additionally, the MMP family is devoted to maintaining ECM homeostasis and collagen formation, which is important for endometriosis fibrosis, suggesting a vital role of MMP1 in AM development. 31 We also found that a variety of collagen associated genes were highly expressed in fibroblasts, including FBLN1 and LUM .…”
Section: Discussionmentioning
confidence: 99%